Marcação diferencial dos argumentos nucleares da língua Ka'apor - Nasle Maria Cabana Ribeiro (2015)
The aim of this thesis is to investigate the role of the particle [ke]that occurs to mark nuclear arguments of transitive and intransitivesentences in the Kaapor language. We show that this particle is not relatedonly to affectedness as described in previous analyses. We noted thatKaapor language has Differential Object Marking (DOM) and alsoDifferential Subject Marking (DSM). DOM is motivated both by thedefiniteness and animacity feature of the object. The particle [ke] appearsenclitic to internal arguments when they exhibit semantic features that arehigh in the animacy and definitenesse scale. On the other hand, the particle[ke] also marks subjects when they receive the thematic role of affectedagent; consequently, the occurrence of this particle is crucial in triggeringDSM in the Kaapor language. Our hypothesis is that this particle has animportant role, as it functions as Case marker that trigger both theDifferential Subject Marking and the Differential Object Marking. In sum,the particle [ke] marks the nuclear arguments that have semantic featuresthat are less expected and, for this reason, these constructions are moresemantically marked. Additionally, we present our proposal that claims thatthere is no one-to-one correspondence between morphological case andabstract Case in Kaapor language.